Environmental psychology: competence and contours of a discipline - Comments based on the contributions (Psicologia USP, 2005)
This text presents a reflective and critical synthesis of the themes of the Symposium Psychology and Environment, as developed by the successive participants. It approaches, initially, the issue of the unity of Environmental Psychology, focusing on its object, role and utility. Next, it discusses Environmental Psychology between disciplinary affirmation and pluridisciplinary errancy. Focusing on the theme Environmental Psychology and Public Policies, it proposes benchmarks for efficient political visibility. Finally, it concludes by presenting a program for the future.